Digital Literacy 5.0 to Enhance Multicultural Education - Anurogo, Dito; Hardin La Ramba; Nabila Diyana Putri; Ulfah Mahardika Pramono Putri; Syarif, Abdillah; Salsabila, Anindya; Karimah, Annisa Ayu; Ilmi, Ahmad Alfarobi Jauharul (Universitas Muhammadiyah Surakarta, 2023)
In Digital Literacy 5.0, the intersectionality of digital competence across various domains marks a paradigm shift from traditional siloed approaches to a more integrated and holistic framework. This article explores the pervasive influence of digital literacy across diverse fields including health, medicine, nutrition, medical tourism, economy, biomedical sciences, bioinformatics, telemedicine, telehealth, artificial intelligence (AI), and vascular surgery. Emphasizing the necessity of digital literacy not just as a skill for tool utilization but as a cornerstone for understanding and leveraging the potential of digital technologies, this comprehensive exploration underscores the critical role of digital competence in enhancing patient outcomes, driving economic growth, spurring innovation, and revolutionizing healthcare and surgical practices. Through a multidisciplinary lens, the article elucidates the indispensability of digital literacy in a technologically interconnected era, highlighting its implications for policy, educational paradigms, and future technological advancements.